Packing simulation and analysis applied to a thermoplastic composite recycling process - Bruneau, Awen; Mahé, François; Binetruy, Christophe; Comas-Cardona, Sébastien; Landry, Charlotte; Durand, Nelly (Frontiers in Materials, 2024)
A numerical model of packing applied to rigid objects is presented. It aims at describing a random stack of polymer composite chips in order to model the packing step of an existing recycling technique. The geometric properties of the stack play a major role in the mechanical properties of the recycled products. Short, simple and effective geometric descriptors of the stack are proposed. Their ability to differentiate random stacks is illustrated with an example. Then, a validation is proposed based on experimental data obtained from a bench specially designed for this work. The tests consist in the free fall of square chips. Finally, the developed model is compared to other models (free fall and packing of fibers) in order to enforce its relevance in the simulation of packing of rigid objects.